Characterization of kinnow (citrus reticulate) peel and its effect on the quality of muffin. Issue 12 (17th May 2022) - Khaleel, Gangavarapu; Sharanagat, Vijay Singh; Singh, Lochan; Kumar, Yogesh; Kumar, Kshitiz; Kishore, Anand; Saikumar, Akuleti; Mani, Sarvanan
Abstract: Kinnow peel powder (KPP) characterization (particle size; <180 μm, 180–250 μm, and 250–500 μm) showed that the particle size under 180 μm posses higher bulk density, color value L* & b*, oil absorption capacity, water solubility, and lower water holding capacity. Total phenolic content, total flavonoid content, and antioxidant properties of KPP varied in the range of 10.1 ± 0.21 to 10.9 ± 0.03 mg GAE/g, 4.96 ± 0.59 to 6.09 ± 0.56 mg QE/g, and 77.5 ± 0.96 to 87.2% ± 0.51%, respectively. An increase in particle size increased the pasting and thermal properties. Highest pasting viscosity (1069 ± 2 cP) and pasting temperature (75.3°C ± 0.10°C) were observed for the largest particle size KPP. Valorization of KPP was achieved by the development of muffins by partial replacement (5%, 10%, 15%, and 20%) of refine wheat flour. An increase in the concentration of KPP in muffins led to a decrease in the volume, color parameters, and increase in hardness. The highest desirability was found at 5% replacement level. Novelty impact statement: The present study was focused on valorization of kinnow peel for the development of muffins. The study will add the scientific data on kinnow peel with respect to different particle size for the development of bakery products.